Generation of human hepatic progenitor cells with regenerative and metabolic capacities from primary hepatocytes - Takeshi Katsuda; Juntaro Matsuzaki; Tomoko Yamaguchi; Yasuhiro Yamada; Marta Prieto-Vila; Kazunori Hosaka; Atsuko Takeuchi; Yoshimasa Saito; Takahiro Ochiya (eLife, 2019)
Hepatocytes are regarded as the only effective cell source for cell transplantation to treat liver diseases; however, their availability is limited due to a donor shortage. Thus, a novel cell source must be developed. We recently reported that mature rodent hepatocytes can be reprogrammed into progenitor-like cells with a repopulative capacity using small molecule inhibitors. Here, we demonstrate that hepatic progenitor cells can be obtained from human infant hepatocytes using the same strategy. These cells, named human chemically induced liver progenitors (hCLiPs), had a significant repopulative capacity in injured mouse livers following transplantation. hCLiPs redifferentiated into mature hepatocytes in vitro upon treatment with hepatic maturation-inducing factors. These redifferentiated cells exhibited cytochrome P450 (CYP) enzymatic activities in response to CYP-inducing molecules and these activities were comparable with those in primary human hepatocytes. These findings will facilitate liver cell transplantation therapy and drug discovery studies.